2017
DOI: 10.1158/1541-7786.mcr-17-0182
|View full text |Cite
|
Sign up to set email alerts
|

EWS/FLI is a Master Regulator of Metabolic Reprogramming in Ewing Sarcoma

Abstract: Ewing sarcoma is a bone malignancy driven by a translocation event resulting in the fusion protein EWS/FLI1 (EF). EF functions as an aberrant and oncogenic transcription factor that misregulates the expression of thousands of genes. Previous work has focused principally on determining important transcriptional targets of EF, as well as characterizing important regulatory partnerships in EF-dependent transcriptional programs. Less is known, however, about EF-dependent metabolic changes or their role in Ewing sa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 55 publications
6
50
0
Order By: Relevance
“…We first investigated the baseline expression of the SSP in Ewing sarcoma cell lines and tumors. In the Cancer Cell Line Encyclopedia (http://www.broadinstitute.org/ccle), PHGDH expression was higher in Ewing sarcoma than in any other cancer, an observation recently reported by others . We measured the expression of SSP enzymes in Ewing sarcoma cell lines using qRT‐PCR and western blot, and observed higher protein expression of pathway components in all cell lines compared with mesenchymal stem cells (MSCs), putative cells of origin for Ewing sarcoma (supplementary material, Figure S3A–C).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…We first investigated the baseline expression of the SSP in Ewing sarcoma cell lines and tumors. In the Cancer Cell Line Encyclopedia (http://www.broadinstitute.org/ccle), PHGDH expression was higher in Ewing sarcoma than in any other cancer, an observation recently reported by others . We measured the expression of SSP enzymes in Ewing sarcoma cell lines using qRT‐PCR and western blot, and observed higher protein expression of pathway components in all cell lines compared with mesenchymal stem cells (MSCs), putative cells of origin for Ewing sarcoma (supplementary material, Figure S3A–C).…”
Section: Resultssupporting
confidence: 55%
“…Of particular relevance to this study, menin was shown to cooperate with cMYC in the regulation of metabolism‐associated genes, including PSAT1 , in an MLL‐independent fashion . Moreover, the EWS–FLI1 oncoprotein itself contributes to maintenance of SSP gene expression in Ewing sarcoma . The extent to which MYC, EWS–FLI1, or other transcriptional regulators cooperate with menin to hijack and maintain oncogenic activation of the SSP in Ewing sarcoma remains to be determined.…”
Section: Discussionmentioning
confidence: 84%
“…Our study complements and extends a recent report by Tanner and colleagues that also described the regulation of de novo serine‐glycine biosynthesis by EWS‐FLI1. Tanner and colleagues presented data using shRNA‐based silencing of EWS‐FLI1 that indicated EWS‐FLI1 regulates PHGDH, PSAT1, and PSPH expression, and that depletion of EWS‐FLI1 decreases the expression of SHMT1/2.…”
Section: Discussionsupporting
confidence: 90%
“…Depletion of EWS‐FLI1 or the silencing or inhibition of PHGDH reduced the GSH/GSSG and NADPH/NADP ratios in EWS cells resulting in increased production of reactive oxygen species in EWS cells (Figure ). Our findings suggest a mechanistic basis for previous observations that have described mitochondrial stress or DNA damage following depletion of EWS‐FLI1 in EWS cells.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation